2014
DOI: 10.1136/neurintsurg-2014-011235.rep
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous approach for the treatment of direct carotid cavernous fistula following Pipeline embolization of cavernous carotid aneurysm: a report of two cases and review of the literature

Abstract: Flow diverters are increasingly used for the endovascular treatment of cerebral aneurysms. A rare complication from flow diversion is delayed aneurysm rupture, which can lead to carotid–cavernous fistula (CCF) in the setting of cavernous carotid aneurysms (CCAs). Direct CCFs pose unique management challenges, given the lack of transarterial access to the fistula. We present two cases of direct CCFs following treatment of CCAs with the Pipeline embolization device (PED). Case 1 was a middle-aged patient with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
0
27
1
Order By: Relevance
“…63 Lin et al presented 2 such cases of direct CCFs that formed as a result of delayed aneurysm rupture following PED treatment of CCA. 43 In cases of posttraumatic and spontaneous CCF, the PED may be a possible treatment option; however, there is a lack of larger studies to confirm the results of the few reported case reports and small series presented here. It should be mentioned that traditional methods such as transvenous and transarterial embolization have an excellent safety-efficacy profile and should continue to be offered as a first-line therapy for these patients.…”
Section: Carotid-cavernous Fistulascontrasting
confidence: 40%
“…63 Lin et al presented 2 such cases of direct CCFs that formed as a result of delayed aneurysm rupture following PED treatment of CCA. 43 In cases of posttraumatic and spontaneous CCF, the PED may be a possible treatment option; however, there is a lack of larger studies to confirm the results of the few reported case reports and small series presented here. It should be mentioned that traditional methods such as transvenous and transarterial embolization have an excellent safety-efficacy profile and should continue to be offered as a first-line therapy for these patients.…”
Section: Carotid-cavernous Fistulascontrasting
confidence: 40%
“…They concluded that intraaneurysmal coil embolization is not an effective treatment option for large or giant CCA. [6] According to a recent report, a flow diverting stent has been developed for the effective treatment of an unruptured giant symptomatic CCA; [7] however, early, [8] and delayed [9,10] rupture of the aneurysm after treatment has been described. The incidence delayed ruptured of an aneurysm after the stent is 0.6-1%, but was not reported for early rupture.…”
Section: Resultsmentioning
confidence: 99%
“…The risk factor is aneurysm size 10 mm or larger. [9] In cases of a ruptured aneurysm with flow divertingstent treatment, the blood flow entered the aneurysm saccontinuously without intra-aneurysmal pressure reductionimmediately after device deployment. Furthermore, it wasnecessary to use the antiplatelet agent during the perioperativeperiod after stenting.…”
Section: Resultsmentioning
confidence: 99%
“…The development of a direct (Barrow type A) CCF after flow diversion is rare, with 8 reported cases in the literature. It has been reported in acute and subacute timeframes after deployment of FDS [16,[65][66][67][68][69]. Management of an intraprocedural CCF after flow diversion is similar to traditional management of such etiologies, including transvenous embolization, parent artery sacrifice and operative methods such as surgical ligation [65,70] or expectant management with ophthalmological evaluation as the guide to further intervention.…”
Section: Thromboembolic and Ischemic Complicationsmentioning
confidence: 99%
“…It has been reported in acute and subacute timeframes after deployment of FDS [16,[65][66][67][68][69]. Management of an intraprocedural CCF after flow diversion is similar to traditional management of such etiologies, including transvenous embolization, parent artery sacrifice and operative methods such as surgical ligation [65,70] or expectant management with ophthalmological evaluation as the guide to further intervention. However, transarterial embolization techniques of the cavernous sinus may be limited in certain cases of flow diversion within the cavernous ICA, since an already-deployed FDS may prevent transarterial access across the stent into the aneurysm or into the rupture site or fistulous connection (Fig.…”
Section: Thromboembolic and Ischemic Complicationsmentioning
confidence: 99%